Phenotype and function of human monocytes remain mainly unaffected by very small superparamagnetic iron oxide particles - Hussein, Sari; Kühl, Anja Andrea; Golusda, Laura; Plattner, Christina; Heinze, Nadine; Sturm, Gregor; Freise, Christian; Traub, Heike; Schannor, Mathias; Trajanoski, Zlatko; Taupitz, Matthias; Siegmund, Britta; et al. (Frontiers in Nanotechnology, 2025)
The field of medical application of organic or inorganic nanoparticles is extensive. Medical nanoparticles offer benefits but pose risks. For safe use in diagnostics and therapy, they should be inert, non-immunogenic, non-aggregating, and avoid long-term accumulation in sensitive tissues like bone marrow or the brain. We have developed in-house very small superparamagnetic iron oxide nanoparticles (VSOP), 7 nm in size, which have been successfully used in preclinical magnetic resonance imaging (MRI) to detect intestinal inflammation, neuroinflammation and atherosclerosis. This study examines nanoparticle effects on human blood cells focusing on monocytes in vitro as a first step toward clinical application. Whole blood and monocytes from healthy donors and patients with inflammatory bowel disease were treated with VSOP in vitro and analyzed for changes in their transcriptome, phenotype and function. RNA sequencing of monocytes identified the transferrin receptor as one of the most significantly downregulated genes after VSOP treatment, likely to limit iron uptake. Whereas whole blood RNA sequencing showed significant changes only in three non-coding genes. CyTOF analysis confirmed that VSOP-treated monocytes remain inactive, with no increased proliferation or altered migration. Metabolically, VSOP uptake enhanced the oxygen consumption rate. This effect was likely due to phagocytosis rather than effects mediated by the VSOP itself, as phagocytosis of latex beads showed comparable results. In summary, the analysis of peripheral blood mononuclear cells and monocytes suggests that VSOP treatment has no major impact on immune cell phenotype or function indicating VSOP as a promising diagnostic tool in MRI for inflammatory bowel disease.